Impact of Crystal Orientation and Conduction Band Nonparabolicity on Diffusion Constant of Nano-scale Si Rectangular Wires - theoretical estimation. Issue 1 (2017) - Omura, Yasuhisa; Sato, Shingo
No abstract available